Built to last : successful habits of visionary companies - Collins, James C. 1958- (HarperBusiness, 2004)
"Drawing upon a six-year research project at the Stanford University Graduate School of Business, Collins and Porras took eighteen truly exceptional and long-lasting companies - they have an average age of nearly one hundred years and have outperformed the general stock market by a factor of fifteen since 1926 - and studied each company in direct comparison to one of its top competitors. They examined the companies from their very beginnings to the present day - as start-ups, as midsize companies, and as large corporations. Throughout, the authors asked: "What makes the truly exceptional companies different from other companies?"" "Collins and Porras go beyond the incessant barrage of management buzzwords and fads of the day to discover timeless qualities that have consistently distinguished outstanding companies. They also provide inspiration to all executives and entrepreneurs by destroying the false but widely accepted idea that only charismatic visionary leaders can build visionary companies."--BOOK JACKET.